OBRAZ DZIEDZICTWA TONYʼEGO GARNIERA W MIEJSKICH MURALACH - LIPIŃSKI, KAMIL (Slavia Occidentalis, 2020)
The article addresses artes memoriae perceived as documentary traces of a spatial project which has slipped to oblivion, namely Une Cité Industrielle by Tony Garnier from 1917, redefined by Cité de Création in the context of urban housing. The movement, revolving around modern philosophies of urban planning and launched at the turn of the 19th and 20th centuries assumed elimination of private property, equality of the working class and division into zones. It also restored the concept of the relations between nature, history of the inhabitants, industrial and historical development of Viollet-Le-Duc functionality and locality. A contemporary cluster of murals creates a mosaic of historical memorial spaces and contributes to Lyon’s development in a new form.